Final Report for a 1994 National Teaching Development Grant : Collaborative Learning Through Computer Conferencing. - Atkinson, Roger (Committee for the Advancement of University Teaching, 1994)
This is a final report for a 1994 National Teaching Development Grant funded by the Committee for the Advancement of University Teaching. The report details the project, listing its major objectives and achievements, and describes the integration of Internet skills into learning processes across subject areas.